SISTEM PERBAIKAN FAKTOR DAYA MOTOR SLIP RING 3 PHASE MENGGUNAKAN KONTROL ARDUINO - Fatur Rivando; Surojo Surojo; Muhammad Iqbal Nugraha (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Power factor is used to determine the quality of electric power. The factor has a parameter of 0-1 where the number 1 can be said to be close to perfect power factor while close to 0 can be said to be less good. power can also be affected by load. With the improvement of the power factor close to 1, the power energy will work optimally. A 3 phase induction motor is an inductive load that requires reactive power. If reactive power cannot be controlled, it will cause low power factor. The study uses a 3 phase slip ring motor as a load, a capacitor bank panel with Arduino mega 2560 control as a power factor improvement, with a value of step 1 = 5 F, step 2 = 10 F and step 3 = 15 F. The power factor of the slip ring motor at a load of 0 Nm before repair is 0.24 with a reactive power of 1106.15 Var. After the capacitor is activated automatically in Step 5, step 1 and 3, the power factor increases to 0.97 with a reactive power of 259.63 Var. The results of the power experiment at 0 Nm load with a power factor improvement of 0.97, the reactive power and current tend to decrease as the power factor value increases, thus making electrical energy more efficient and optimal.